Psychodynamic case formulations : reflections of a neophyte therapist's experiences of how developing and using a psychodynamic formulation may have influenced treatment?,Psychodynamic case formulations : how do they influence therapeutic work? - Tebbutt, Hayley Lynne (Rhodes University, Faculty of Humanities, Department of Psychology, 2013)
Although it is generally acknowledged and accepted that case formulations are useful in psychotherapy treatment, there is significantly little research illustrating how case formulations are useful in treatment. Research also suggests that case formulations are seldom used in practice after initial training (Eells, 1997; Sim, Gwee, & Bateman, 2005). This research was premised on a particular case study which appeared to highlight shifts in psychotherapy treatment in the sessions directly after the writing or revising of the case formulation, thus prompting the inquiry into the influence of the case formulation on therapeutic work. The research utilised a qualitative methodology and focused on a single case which was a 19 year old university student who expressed a problem with binge eating. The data was drawn from five original and revised case formulations. The participant was seen for 27 therapy sessions, over which time five case formulations were developed and revised. The findings in this study highlight the process of how a psychodynamic case formulation can influence therapeutic work, as reflected in three broad themes of adherence to the case formulation, the confidence of the therapist, and using the formulation as an intervention. The study contributes to arguments for the revival of the case formulation as a necessary therapeutic tool.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Psychodynamic psychotherapy; Psychiatry -- Case formulation; Eating disorders